Implikasi Dari Sanksi Administrasi Terhadap Penerimaan Pajak Kendaraan Bermotor (Studi Kasus Pada Samsat Renon Denpasar) - I Kadek Denny Harta Dwipayana; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2020)
In realizing the national development mission, one of the efforts made by the Indonesian government is to maximize the source of funding in the form of taxes. The state is not categorized as a power state. One type of tax that has the potential to increase along with technological advances and the standard needs of secondary to primary is the motor vehicle tax. The problems of this research are 1) How is the imposition of administrative sanctions on motor vehicle tax receipts at the SAMSAT Renon Denpasar Office? 2) What are the implications of administrative sanctions on motor vehicle tax at the Renon Denpasar SAMSAT Office? The research method used is an empirical legal research method, with data sources using empirical sociological or juridical problem approaches in other words solving secondary problems first then primary. The results of the study can be concluded that: Imposing sanctions for motorcycle tax administration in the SAMSAT Renon Denpasar office can be said to be good, this is seen from the level of compliance of motor vehicle taxpayers in paying motor vehicle tax taxpayers aware of their obligations to pay Motor Vehicle Tax and timely payment Motor Vehicle Tax. Implications of imposing motor vehicle tax administration sanctions based on the results of a regression analysis that with the motor vehicle tax administration sanctions will increase taxpayer compliance